Characterization and application of a coating of starch extracted from avocado (Persea americana L. cv. Hass) seeds as an alternative to reduce acrylamide content in French fries (2022)
ABSTRACT: The starch extracted from avocado (Persea americana L. cv. Hass) seeds was characterized and used in the preparation of an edible coating to reduce the oil uptake and acrylamide content in French fries. Starch characterization was carried out using Differential Scanning Calorimetry, Fourier transform infrared spectrophotometry, gelatinization, and scanning electron microscopy. Uncoated (UFF) and coated (CFF) French fries were compared and evaluated for moisture, water activity (Aw), fat, color, firmness, acrylamide content, and sensorial analysis. The extracted starch presented a high crystalline structure and good stability to mechanical work and heat treatments. The CFF French fries showed significantly higher Aw, color parameter a*, but lower luminosity and acrylamide content than UFF samples. Similarly, the CFF samples tended to decrease the fat content, although without statistical differences. Avocado seed starch can be an economical and technically feasible alternative to the food industry as an effective coating to reduce acrylamide content in French fries.